Translation, Interpretation, and Common Meaning: Victoria Welby’s Significal Perspective - Petrilli, Susan (TTR)

(untitled) (Association canadienne de traductologie, 2007)
AbstractAs she worked through the nineteenth century Victoria Welby elaborated a fascinating theory of translation based on her theory of sign and meaning, which she designated with the term significs. This means to say that, on the one hand, Welby’s theory of translation took account of the vastness and variety of the world of signs, therefore of the unbounded nature of translative-interpretive processes which cannot be limited to the mere transition from one language to another. The condition for interlingual translation in the human world is the larger context where translative processes converge with life processes and maybe push beyond in what would seem to be an unbounded cosmic dimension. On the other hand, that Welby should have related her translation theory to her theory of sign and meaning also implies that she founded her translation theory in a theory of value recognizing the inevitable importance of the latter when translating within a single language as much as across different languages in a plurilingual and intercultural world. Ultimately, in the properly human world, to translate means to interpret, that is, to translate transfiguring and transvaluating significance.